Protection of Nursing Students from Harassment During Field Practice - Audia Destiana; Claudia Natali Armeta; Fira Puspita Sari; Resti Puspitasari (Immortalis Journal of Interdisciplinary Studies, 2025)
Harassment of nursing students during field practice has become a serious issue threatening the comfort and safety of the learning process. This phenomenon is influenced not only by the imbalance of power relations and the persistent patriarchal culture, but also by the suboptimal legal and institutional protections in educational and healthcare environments. This study aims to identify the factors causing harassment against nursing students and evaluate the protective efforts provided by educational institutions and healthcare facilities. The method used is qualitative with a literature study approach, examining various laws and related literature to obtain a comprehensive picture of the issue. The research results show that although there are regulations such as Law Number 12 of 2022 concerning Sexual Violence Crimes and the Minister of Education, Culture, Research, and Technology Regulation Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education, the implementation on the ground is still not optimal. Structural factors, a work culture that is not supportive, and a lack of reporting systems are the main obstacles. Institutional protection efforts are still administrative in nature and have yet to be fully integrated between educational institutions and health facilities. The implications of this research emphasize the importance of strengthening inter-agency coordination, increasing awareness and sensitivity training regarding harassment issues, and developing stricter and more comprehensive policies. Educational institutions and health facilities must work together to create a safe and violence-free practice environment.